Surgical Orthodontic Treatment of an Impacted Canine in the Presence of Dens Invaginatus and Follicular Cyst - Marialuce Spallarossa; Carola Canevello; Francesca Silvestrini Biavati; Nicola Laffi (Case Reports in Dentistry)
Introduction. “Dens invaginatus” is a dental anomaly which originates from the invagination of the ameloblastic epithelium into the lingual surface of the dental crown during the odontogenesis. It can cause early pulpal necrosis, abscesses, retention or dislocation of contiguous elements, cysts, and internal resorptions. It normally affects the upper lateral incisors. In the following study the authors will discuss the etiology, the physiopathology, and the surgical-orthodontic management of a rare case of impacted canine associated with dens invaginatus and follicular cyst, with the aim of highlighting the importance of taking any therapeutic decision based on the data available in the literature. Case Report. The present study describes a combined surgical-orthodontic treatment of an impacted canine associated with a lateral incisor (2.2) suffering from type III dens invaginatus with radicular cyst, in a 15-year-old patient. Discussion. When treating a dens invaginatus there are different therapeutic solutions: they depend on the gravity of the anomaly and on the association with the retention of a permanent tooth. The aesthetic and functional restoration becomes extremely important when performing a surgical-orthodontic repositioning.